ANALISIS IMPLEMENTASI KEBIJAKAN INTERVENSI GIZI SENSITIF DALAM MENURUNKAN KEJADIAN STUNTING DI KABUPATEN BOGOR - Arfaly Adyatama Putra (2022)
The prevalence of under-fives experiencing stunting in Indonesia according to the 2018 RISKESDAS is 30.8% and the 2021 SSGI is 24.4%. The prevalence of stunting said to be low if stunting are less than 20% of the total under-five population in an area. As a form of government effort in preventing and reducing stunting in Indonesia, the government through the Ministry of National Development Planning/Bappenas has established Guidelines for Implementing Integrated Stunting Reduction Interventions in Regency/Cities. The Central Government requires all regencies/cities to reduce the incidence of stunting through specific and sensitive nutrition interventions. This paper aims to analyze the implementation of sensitive nutrition intervention policies in reducing stunting in Bogor Regency using the Retrospective Analysis Model. The research method used is a qualitative research method. The study describes the details of the implementation of sensitive nutrition intervention policies through programs or activities carried out by the Bogor Regency Government. Research data was collected through direct observation, in-depth interviews with RO or related parties, as well as literature studies from various sources related to the research. Based on the research results, it is explained that the Bogor Regency Government has implemented policies through sensitive nutrition intervention programs or activities based on the Implementation Guidelines for Integrated Stunting Reduction Interventions in Regency/City. The results of this study are also expected to be used as material for evaluation and reference in developing science and research, especially in the field of nutrition policy